Comparison of self-reported scales and structured interviews for the assessment of depression in an urban male working population in Japan: a cross-sectional survey - Kadotani, Tomiko; Kadotani, Hiroshi; Arai, Honami; Takami, Masanori; Ito, Hiroyasu; Matsuo, Masahiro; Yamada, Naoto (Sleep science and practice, 2017)
Background The present study aimed to analyze the association among depression, sleep quality, and quality of life using the Japanese version of the Structured Clinical Interview for DSM-IV Axis I Disorders Non-Patient Edition (SCID-I/NP), and to compare these findings with those obtained using self-reported scales, in an urban male working population in Japan. Methods The present study included 324 middle-aged participants (43.8 ± 8.37 years) (participation rate: 69.5%). The Japanese version of the SCID-I/NP was administered by a single physician. Self-reported scales, including the Zung Self-Rating Depression Scale (SDS), Epworth Sleepiness Scale (ESS), Pittsburgh Sleep Quality Assessment (PSQI), and 36-item Short-Form Health Survey (SF-36) were used to assess depression, sleepiness, sleep quality, and quality of life, respectively. Participants were then divided into a major depressive disorder (MDD) and control group based on the results of structured interviews, following which self-reported scale scores were compared between the two groups. Results A total of 24 participants met criteria for MDD based on responses during structured interviews (current: 4; past: 20). Patients with MDD did not report feeling sleepier than those without psychiatric disorders (controls) (ESS: P = 0.184), although they experienced slightly poorer sleep quality (PSQI: P = 0.052). In addition, participants of the MDD group exhibited lower SF-36 subscale scores for general health ( P = 0.002), vitality ( P < 0.001), social functioning ( P < 0.001), role emotional ( P = 0.004), and mental health ( P < 0.001) domains, and higher SDS scores ( P = 0.038) compared to controls. The area under the receiver (AUC) operating characteristic curve for the detection of MDD was 0.631 and 0.706 for the SDS and mental health subscales, respectively. Conclusions Our findings indicate that patients with MDD exhibit slightly poorer sleep quality and significantly poorer quality of life compared to controls, and that the SF-36 may be used as an alternative to the SDS to screen for depression in an urban male working population in Japan.